Pengaruh Persepsi Kepemimpinan, Innovative Work Behaviour Terhadap Workforce Agility pada Perusahaan - Khairunnisa, Shania Febriana; Setiasih (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
In a Constantly evolving and competitive era, companies are faced with demands to be more responsive and adaptive to rapid change. The company's ability to adapt and innovate is the key to success in facing these challenges. In this context, leadership perceptions and innovative work behavior are important factors that can affect the agility of the workforce in the company. Therefore, this study aims to investigate the influence of leadership perceptions and innovative work behavior on Workforce agility in the company. This study uses a quantitative approach with a survey research design. Data were collected through questionnaires distributed to employees of leather manufacturing companies. The research sample was selected using accidental sampling technique. The data collected were then analyzed using multiple linear regression tests. The results showed that leadership perceptions had no effect on Workforce agility in the company. While innovative work behavior affects Workforce agility in the company. The more dominant factors are organizational structure, workday habits, management system, and employee engagement. However, innovative work practices reveal significant improvements in worker agility. To enable rapid adaptation to economic and technological changes, companies must encourage innovative work practices among their employees. Workforce agility can be improved across the board by fostering trust, providing respect, and providing space for innovative employees. The implications and implications of this study suggest that it is critical for businesses to develop strategies that consider these factors to improve the day-to-day operations and adaptability of organizations.